INKLUSI PAJAK TERINTEGRASI MATAPELAJARAN MEMBANGUN BUDAYA SADAR PAJAK SEJAK DINI - Ridhuan, Syamsu; Ningsih, Rahmah; Angela, Nofia (Jurnal Pengabdian Masyarakat AbdiMas, 2021)
The partner of community service activities is the Al-Khasyi’un Islamic Junior High School educational institution in Cipayung Subdistrict, Ciputat District, South Tanggerang City, Banten Province. The problem found is that the study of tax inclusion has not been implemented as a national program with integrated subjects. The solution needs to be socialized by conducting training activities for teachers. The goal is for teachers, after participating in socialization activities and training of trainers, to be able to transform their knowledge of tax inclusion in order to build a tax -aware culture from an early age. Methods of implementation, in the form of socialization and training of coaches, to train teachers to become coaches of integrated tax inclusion subjects. media tax inclusion learning materials as well as conducting socialization and training for teachers. It is hoped that the DGC institutions of the Ministry of Ministry of Education and Ministry of Education can follow up by making a pilot project of tax inclusion learning with the learning media that has been developed in more junior high schools in Indonesia. Keywords: tax inclusion, tax awareness, early